2021
DOI: 10.1016/j.sjbs.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the standards compliance of the queen bees reared in the Mediterranean region in Turkey

Abstract: The influence of different commercial queen producers on the quality of Apis mellifera queens was assessed. It was aimed to determine the quality characteristics of queens reared by commercial queen producers located in the province of Antalya, which is an important region in queens production due to its climatic characteristics. For this purpose, the quality characteristics of a total of 105 queen bees obtained from 21 enterprises were determined. Differences between the enterprises in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…In a previous study, similar results were obtained in the averages of the emergence weight of the queens reared from 1-day old larvae (Ozmen Ozbakır, 2021). The live weight of the queens varied between 171-223 mg in the queens obtained from commercial queen rearing enterprises (Arslan et al, 2021). The results of the current study were found to be lower than the average weights at the emergence of Italian queens (Faccini et al, 2021) and Caucasian queens (Kahya et al, 2008).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In a previous study, similar results were obtained in the averages of the emergence weight of the queens reared from 1-day old larvae (Ozmen Ozbakır, 2021). The live weight of the queens varied between 171-223 mg in the queens obtained from commercial queen rearing enterprises (Arslan et al, 2021). The results of the current study were found to be lower than the average weights at the emergence of Italian queens (Faccini et al, 2021) and Caucasian queens (Kahya et al, 2008).…”
Section: Resultssupporting
confidence: 88%
“…The number of ovarioles was similar to the values reported by Kahya et al (2008), Jackson et al (2011), Gregorc & Smodis Skerl (2015), and Walsh et al (2021) but higher than those reported by Faccini et al (2021). In the current study, the spermathecal diameter of the queens was similar to the values reported in many studies (Akyol et al 2008;Kahya et al, 2008;Arslan et al, 2021) but was lower than those reported by Faccini et al (2021).…”
Section: Resultssupporting
confidence: 88%
“…For this reason, the most important member of a honey bee colony is the queen [5,6], and queen quality is a critical factor for successful beekeeping [7]. In beekeeping, it is a very important advantage to start with the use of quality breeders and qualified queens for economical beekeeping [8]. The characteristics that will be transferred to future generations through queen bees are of great importance in terms of colony behavior and productivity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some researchers divided the queen bees into 3 groups according to their body weight: heavy (200 mg and above), medium (between 190-200 mg), and light (190 mg and below), and accepted the queens with 200 mg or more as high quality [24,25]. Many researchers agree that spermatheca capacity increases due to the decrease in larval age in queen rearing [8,25,26]. A queen's productivity and longevity depend on the queen's ability to store spermatozoa and the size of the spermatheca [27].…”
Section: Introductionmentioning
confidence: 99%
“…The number of spermatozoa in spermatheca is crucial for the longevity and reproductive success of the queen. The number of spermatozoa in the spermatheca is one of the most common quality indicators of the queen (Kahya et al, 2008;Hatjina et al, 2014;Delaney et al, 2010;Arslan et al, 2021). The naturally mated queens have an average of 4-6 million spermatozoa in their spermatheca (Woyke, 1962(Woyke, , 1983.…”
Section: Introductionmentioning
confidence: 99%